Made in Germany? Art and identity in a global nation - Roth, Lynette 1976-; Bell, Natalie 1967- (Harvard Art Museums, 2024)
"Made in Germany? takes an unprecedented look at German art after 1980, arguing for a more expansive idea of what it means to be German. The catalogue presents artworks in a range of media-film, video, photography, painting, printmaking, drawing, collage, and installation-by artists from different generations and diverse backgrounds. Uniting these varied works is the question: Who or what represents Germany today?"--Back cover
Aus dem Impressum: "This book accompanies the exhibition 'Made in Germany? Art and identity in a Global Nation', on view at the Harvard Art Museums, Cambridge, Massachusetts, from September 13, 2024 through January 5, 2025."
Keywords: Geschichte 1980-2024; Identität -- Motiv; Kunst; Deutschland; 21st century; 20th century; Art, German / 21st century / Exhibitions; Art, German / 20th century / Exhibitions; Identity (Psychology) / Germany / Exhibitions; Art allemand - 20e siècle - Expositions; Identité (Psychologie) - Allemagne - Expositions; Art, German / https://id.worldcat.org/fast/816307; Identity (Psychology) / https://id.worldcat.org/fast/966892; stickers; exhibition catalogs; Exhibition catalogs / https://id.worldcat.org/fast/1424028; Exhibition catalogs; Catalogues d'exposition; Germany / https://id.worldcat.org/fast/1210272; Ausstellungskatalog -- Harvard Art Museums -- 13.09.2024-05.01.2025 -- Cambridge, Mass.; Aufsatzsammlung